Poly(butylene succinate)/bamboo powder blends as solid-phase carbon source and biofilm carrier for denitrifying biofilters treating wastewater from recirculating aquaculture system - Liu, Dezhao (Sci Rep, 2018)
In this study, Poly(butylene succinate)/bamboo powder (PBS/BP) was newly applied and tested for 8 months as the carbon source in two moving bed reactors for nitrate removal in real RAS wastewater (fresh/sea water), with the purposes of simultaneous reducing the cost of PBS packing and effluent DOC. Fast start-ups were obtained in both reactors, in which high denitrification rates were observed (0.68 ± 0.03 and 0.83 ± 0.11 kg [Formula: see text] -N m(−3) d(−1) for fresh and sea water, respectively) with no nitrite and low ammonia accumulation. Reduced DOC concentrations in the effluents were also observed compared to pure PBS. The freezing of PBS/BP showed a further slower release of DOC, which might be beneficial to the life of the PBS/BP for the denitrification process, however, microbial activity, especially in high salinity wastewater, was observed to have declined. Illumina sequencing revealed that the autotrophic genus arcobacter was discovered first time in solid-phase denitrification system with salinity. Redundancy analysis (RDA) was used to reveal the relationships between environmental factors and the microbial community. In overall, PBS/BP blends were proven to be an economically attractive carbon source for nitrate removal in RAS.